2005
DOI: 10.1161/01.str.0000170717.91591.7d
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Presentation and Outcome in Developing Countries

Abstract: Background and Purpose-Despite increasing burden of stroke in Africa, prospective descriptive data are rare. Our objective was to describe, in The Gambia, the clinical outcome of stroke patients admitted to the Royal Victoria Teaching Hospital in the capital Banjul, to assess mortality and morbidity, and propose preventive and therapeutic measures. Methods-Prospective data were collected on consecutive patients older than 15 years old admitted between February 2000and February 2001 with the diagnosis of nonsub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
111
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(131 citation statements)
references
References 18 publications
15
111
0
1
Order By: Relevance
“…This average age is close to that of a predominantly black American population [8] studies favored a male preponderance with a ratio between 1.3 and 1.5 [13] [14] [15]. Ratios to 2 have been described [10], as well as a female preponderance with ratios between 0.82 and 0.97 [16] [17]. The predominance was female in our study with a sex ratio of 0.92.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This average age is close to that of a predominantly black American population [8] studies favored a male preponderance with a ratio between 1.3 and 1.5 [13] [14] [15]. Ratios to 2 have been described [10], as well as a female preponderance with ratios between 0.82 and 0.97 [16] [17]. The predominance was female in our study with a sex ratio of 0.92.…”
Section: Discussionsupporting
confidence: 84%
“…Immediate evolution: patients who had hemorrhagic stroke were all transferred to an intensive care unit and some ischemic stroke (15.18%). The evolution was marked by a death in 20.25% (16) cases. The Table 3 shows the distribution of patients according to paraclinical characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…15 The high mortality rate substantiates that the majority of the 5.7 million deaths attributed to stroke annually occur in low-and middle-income countries. 16 The short hospital stay and few physiotherapy treatment sessions received during hospitalisation could have contributed to the poor patient functional ability and high case fatality.…”
mentioning
confidence: 90%
“…This high death toll is even much more in SSA where mortality and case fatality rates are alarming ranging from 21% to as much as 50.6% [24][25][26][27][28][29][30][31][32][33][34]. In addition, stroke has also been noted to be a major cause of unregistered deaths in many developing countries [14,16].…”
Section: Epidemiology Of Stroke In Africamentioning
confidence: 99%
“…In fact, until recently many tertiary/referral hospitals in sub Saharan Africa did not have CT scan machines [24,37]. Few stroke persons were opportune to have a CT scan viz: 5.83% 24, 11.11% [62] in Nigeria, 10% from Madagascar [63] and even 0% from Gambia [64]. More recently, the percentages are increasing gradually as one Nigerian study showed that 40.8% patients had CT brain, while 5.6% had magnetic resonance imaging (MRI) [65] and 34.9% in Zimbabwe [60].…”
Section: Action Taken In the Care Of Stroke In Sub Saharan Africamentioning
confidence: 99%